Glutathione biosynthesis in Arabidopsis trichome cells - Gutiérrez-Alcalá, G; Gotor, C; Meyer, A; Fricker, M; Vega, J; Romero, L (National Academy of Sciences, 2000)
In Arabidopsis thaliana, trichome cells are specialized unicellular structures with uncertain functions. Based on earlier observations that one of the genes involved in cysteine biosynthesis (Atcys-3A) is highly expressed in trichomes, we have extended our studies in trichome cells to determine their capacity for glutathione (GSH) biosynthesis. First, we have analyzed by in situ hybridization the tissue-specific expression of the genes Atcys-3A and sat5, which encode O-acetylserine(thio)lyase (OASTL) and serine acetyltransferase (SAT), respectively, as well as gsh1 and gsh2, which encode γ-glutamylcysteine synthetase and glutathione synthetase, respectively. The four genes are highly expressed in leaf trichomes of Arabidopsis, and their mRNA accumulate to high levels. Second, we have directly measured cytoplasmic GSH concentration in intact cells by laser-scanning microscopy after labeling with monochlorobimane as a GSH-specific probe. From these measurements, cytosolic GSH concentrations of 238 ± 25, 80 ± 2, and 144 ± 19 μM were estimated for trichome, basement, and epidermal cells, respectively. Taking into account the volume of the cells measured using stereological techniques, the trichomes have a total GSH content more than 300-fold higher than the basement and epidermal cells. Third, after NACl treatment, GSH biosynthesis is markedly decreased in trichomes. Atcys-3A, sat5, gsh1, and gsh2 mRNA levels show a decrease in transcript abundance, and [GSH] cyt is reduced to 47 ± 5 μM. These results suggest the important physiological significance of trichome cells related to GSH biosynthesis and their possible role as a sink during detoxification processes.